Contrasting the dynamics of elastic and non-elastic deformations across an experimental colloidal Martensitic transition. Issue 27 (14th June 2017) - Ganguly, Saswati; Mohanty, Priti S.; Schurtenberger, Peter; Sengupta, Surajit; Yethiraj, Anand
Abstract : We present a framework to segregate the roles of elastic and non-elastic deformations in the examination of real-space experiments of solid–solid Martensitic transitions. Abstract : We present a framework to segregate the roles of elastic and non-elastic deformations in the examination of real-space experiments of solid–solid Martensitic transitions. The Martensitic transformation of a body-centred-tetragonal (BCT) to a body-centred-orthorhombic (BCO) crystal structure has been studied in a model system of micron-scale ionic microgel colloids (P. S. Mohanty, P. Bagheri, S. Nöjd, A. Yethiraj and P. Schurtenberger, Phys. Rev. X, 2015, 5, 011030). Non-affine fluctuations, i.e., displacement fluctuations that do not arise from purely elastic (affine) deformations, are detected in particle configurations acquired from the experiment. Tracking these fluctuations serves as a highly sensitive tool in signaling the onset of the Martensitic transition and precisely locating particle rearrangements occurring at length scales of a few particle diameters. Particle rearrangements associated with non-affine displacement modes become increasingly favorable during the transformation process. The nature of the displacement fluctuation modes that govern the transformation are shown to be different from those predominant in an equilibrium crystal. We show that BCO crystallites formed through shear may, remarkably, co-exist with those resulting from local rearrangements within the same sample.